Thermal Plasticity of the Kelp Laminaria digitata (Phaeophyceae) Across Life Cycle Stages Reveals the Importance of Cold Seasons for Marine Forests - Liesner, Daniel; Shama, Lisa N. S.; Diehl, Nora; Valentin, Klaus; Bartsch, Inka (Frontiers in Marine Science, 2020)
Phenotypic plasticity (genotype x environment interaction) is an especially important means for sessile organisms to cope with environmental variation. While kelps, the globally most productive group of seaweeds, generally possess a wide thermal performance range, kelp populations at their warm distribution limits are threatened by ocean warming. Here, we investigated effects of temperature during ontogeny of the kelp Laminaria digitata across haploid gametophyte and diploid sporophyte life cycle stages in five distinct genetic lines. We hypothesized that thermal plasticity increases trait performance of juvenile sporophytes in experimental temperatures that match the temperature experienced during gametogenesis and recruitment, and that plasticity differs among genetic lines (genetic variation for plasticity). We applied a full-factorial experimental design to generate different temperature histories by applying 5°C and 15°C during meiospore germination, gametogenesis of parental gametophytes and recruitment of offspring sporophytes (19–26 days), and juvenile sporophyte rearing (91–122 days). We then tested for thermal plasticity among temperature history treatments at 5°C and 15°C in a final 12-day experiment assessing growth, the storage compound mannitol, carbon and nitrogen contents, and fluorometric responses in 3–4 month old sporophytes for five genetic lines. Our study provides evidence for the importance of cold temperatures at early development on later sporophyte performance of L. digitata. Gametogenesis and recruitment at 5°C promoted higher growth of offspring sporophytes across experimental temperatures. While photosynthetic capacity was higher at 15°C, carbon and nitrogen storage were higher at 5°C, both showing fast acclimation responses. We identified an important role of genetic variation for plasticity in shaping L. digitata’s thermal plasticity. Trait performance at 5°C or 15°C (reaction norm slopes) differed among genetic lines, even showing opposite response patterns. Interestingly, genetic variation for plasticity was only significant when sporophytes were reared at 5°C. Thus, we provide evidence that the cold-temperate to Arctic kelp species, L. digitata, which possesses a wide temperature tolerance between 0°C and 23°C, is impaired by warm temperature during gametogenesis and recruitment, reducing growth of juvenile sporophytes and expression of variable thermal plasticity in the wild.